PRODUÇÃO DE AÇÚCARES FERMENTÁVEIS POR PRÉ-TRATAMENTO ÁCIDO DILUTO DE FOLHAS DE CANA-DE-AÇÚCAR COM MÍNIMA DEGRADAÇÃO DE AÇÚCAR - Bueno, Danilo; Santos, Chayenne; Sant'Anna, Celso; Brienzo, Michel (ENERGIA NA AGRICULTURA, 2023)
XYLOSE PRODUCTION BY DILUTE ACID PRETREATMENT OF SUGARCANE LEAVES WITH MINIMUM SUGAR DEGRADATION PRODUCTS DANILO BUENO1, CHAYENNE SANTOS2, CELSO SANT’ANNA2, MICHEL BRIENZO1 1 Institute for Research in Bioenergy (Ipben), São Paulo State University (Unesp), Rio Claro, SP, 13500-230, Brazil. danilo.bueno1@unesp.br; michel.brienzo@unesp.br 2 Laboratory of Microscopy Applied to Life Science (Lamav), National Institute of Metrology, Quality and Technology (Inmetro), Duque de Caxias, RJ, 25250-020, Brazil. chaysantos@gmail.com; celso.santanna2@gmail.com ABSTRACT: Xylose is a monosaccharide produced from biomass by acid pretreatment that can be converted into several by-products of value-added. Using response surface methodology, this study evaluated the acid pretreatment of sugarcane leaves to obtain a high xylose yield with a minimum generation of furfural (degradation product). The studied variables were: sulfuric acid concentration, reaction time, and solid/liquid rate in a study region 1 (10-50% m/m of acid, 20-60 min, 32-8% m/v), and a study region 2 (50-70% m/m of acid, 20-50 min, 3-7% m/v). The sugarcane leaves present 37.47% of cellulose, 29.69% of hemicellulose, and 12.24% of lignin. Maximum xylose production (52.82%) was observed with a minimum generation of furfural (1.7%), applying specific conditions of pretreatment containing acid (50% mass/mass - m/m, or 1% mass/vol - m/v), reaction time (60 min) and solid rate/liquid (8% m/v). The highest xylose yields (above 40%) occurred with the application of higher acid concentrations (above 1% m/v or 50% m/m), the most important variable observed in this study. This study pointed to process conditions for xylose production, and such parameters that can be used in the process of obtaining high added-value products by xylose conversion. Keywords: sugarcane, biomass, pretreatment, xylose, chemical composition, fermentable sugar. PRODUÇÃO DE AÇÚCARES FERMENTÁVEIS POR PRÉ-TRATAMENTO ÁCIDO DILUTO DE FOLHAS DE CANA-DE-AÇÚCAR COM MÍNIMA DEGRADAÇÃO DE AÇÚCAR RESUMO: A xilose é um monossacarídeo produzido a partir da biomassa por pré-tratamento ácido que pode ser convertido em diversos subprodutos de valor agregado. Utilizando a metodologia de superfície de resposta, este estudo avaliou o pré-tratamento ácido de folhas de cana-de-açúcar para obter um alto rendimento de xilose com mínima geração de furfural (produto de degradação). As variáveis ​estudadas foram: concentração de ácido sulfúrico, tempo de reação e taxa sólido/líquido em uma região de estudo 1 (10-50% m/m de ácido, 20-60 min, 32-8% m/v), e região de estudo 2 (50-70% m/m de ácido, 20-50 min, 3-7% m/v). As folhas da cana-de-açúcar apresentam 37,47% de celulose, 29,69% de hemicelulose e 12,24% de lignina. Produção máxima de xilose (52,82%) foi observada com geração mínima de furfural (1,7%), aplicando condições específicas de pré-tratamento contendo ácido (50% m/m massa/massa ou 1% m/v massa/volume), tempo de reação (60 min) e taxa de sólidos/líquido (8% m/v). Os maiores rendimentos de xilose (acima de 40%) ocorreram com a aplicação de maiores concentrações de ácido (acima de 1% m/v ou 50% m/m), a variável mais importante observada neste estudo. Este estudo apontou condições de processo para produção de xilose e parâmetros que podem ser utilizados no processo de obtenção de produtos de valor agregado pela conversão de xilose. Palavras-chave: cana-de-açúcar, biomassa, pré-tratamento, xilose, composição química, açúcar fermentável.